Evolving public expenditure in Chinese agriculture: Definition, pattern, composition, and mechanism - Yu, Bingxin; Chen, Kevin Z.; Zhang, Yumei; Zhang, Haisen (International Food Policy Research Institute, 2014)
The Chinese economy has recently experienced a rapid and fundamental transformation, and the public expenditure on agriculture has also changed to reflect shifts in policy priorities. This paper reviewed public agricultural expenditure in a comprehensive way using detailed expenditure data at different administrative levels. The paper found that public expenditure for agriculture has increased steadily in China; however, the definition of agricultural spending might not precisely measure resources allocated to agricultural production. Some unique features of Chinese agricultural expenditure are identified, namely high decentralization and substantial intergovernmental transfer. The highly decentralized and hierarchical administrative system caused fragmentation in budget and implementation, resulting in rampant inefficiencies. Government expenditure also exhibits considerable regional disparity. This study recommends improving the fiscal system by rebalancing expenditure with revenues, prioritizing agricultural expenditure, and addressing regional disparities.